Thermal Stress Affects Gonadal Maturation by Regulating GnRH, GnRH Receptor, APGWamide, and Serotonin Receptor Gene Expression in Male Pacific Abalone, Haliotis discus hannai During Breeding Season - Sukhan, Zahid Parvez; Sharker, Md. Rajib; Cho, Yusin; Hossen, Shaharior; Choi, Kap Seong; Kho, Kang Hee (Frontiers in Marine Science, 2021)
Temperature has crucial effects on gonadal development and reproduction of abalone. To understand the impact of thermal stress on molecular and physiological process triggering the regulation of reproduction, changes in mRNA expression of neuroendocrine genes encoding two abalone gonadotropin-releasing hormone (Hdh-GnRH, Hdh-GnRH-like peptide), GnRH receptor (Hdh-GnRH-R), Hdh-APGWamide, and serotonin receptor (5-HThdh) were examined in ganglia and testis of male Pacific abalone (Haliotis discus hannai). Abalones were exposed to low water temperature (LWT) and high water temperature (HWT) in early and peak breeding season for 7 days. Levels of testosterone in hemolymph were also measured during peak breeding season after exposure to temperature. Gonadosomatic index did not show any significant changes during early breeding season after any temperature treatment. However, it was significantly decreased in LWT or HWT exposed abalone compared to normal water temperature (NWT) group during peak breeding season. In the early breeding season, mRNA expression of all five genes were decreased in LWT and increased in HWT exposed abalone on day-7. These changes were significant between LWT and HWT groups. In peak breeding season, compared to the NWT group, the mRNA expression of Hdh-GnRH-like peptide was significantly decreased in CG and testis in both LWT and HWT groups of abalone. Hdh-GnRH gene expression was also significantly decreased in PPG and BG of both LWT and HWT groups. However, Hdh-GnRH-R expression was significantly decreased in all tested tissues except BG. Hdh-APGWamide gene expression was found to be decreased significantly in PPG and testis of both LWT and HWT groups. Interestingly, the expression of 5-HThdh was significantly increased in the HWT group but decreased in the LWT group. Hemolymph levels of testosterone were significantly decreased in the HWT group. However, its changes were insignificant in the LWT group compared with the NWT group. These results suggest that a high temperature might be a stressful condition for abalone whereas a low temperature might be physiologically acceptable condition or less stressful for abalone. Altogether, these results denote that thermal stress has a repressive effect on gonadal maturation and reproduction by regulating expression of Hdh-GnRH-like peptide, Hdh-GnRH, Hdh-GnRH-R, Hdh-APGWamide, and 5-HThdh genes.